Whole-Body Mechanics of Double-Leg Attack in Elite and Non-elite Male Freestyle Wrestlers - Yamashita, Daichi; Arakawa, Hiroshi; Wada, Takahiro; Yumoto, Kenichi; Fujiyama, Kotaro; Nagami, Tomoyuki; Shimizu, Seshito (Frontiers in Sports and Active Living, 2020)
This study examined the movement characteristics of the double-leg attack in elite and non-elite wrestlers. Twenty light-weight male wrestlers were divided by skill level: Elite group (n = 11) who participated in international-level competitions and Non-Elite group (n = 9) consisting of college-level wrestlers. Each wrestler performed the double-leg attacks against a defender. Three-dimensional coordinates of anatomical landmarks and the ground reaction force (GRF) of the trailing limb were analyzed. The forward velocity and displacement of the whole-body center of mass (COM) and the 7th cervical spine (C7), which represents the upper body, were calculated. Additionally, joint torques were calculated by a standard inverse dynamics method. No significant differences were observed between groups for movement duration and the C7 forward displacement, which relates to the interpersonal distance. Still, they were significantly correlated in the non-elite wrestlers, as well as in all wrestlers (r = 0.78, p < 0.05 and r = 0.65, p < 0.01, respectively). While there were no group differences in joint angles at both limbs and torques at the trailing limb, the time-to-peak resultant GRF was shorter, and peak resultant GRF was greater at the trailing limb in the elite wrestlers compared to that in the non-elite wrestlers (p < 0.05). There were no group differences in peak forward velocity of the COM and the C7. However, the C7 forward velocity at 0.20, 0.25, and 0.30 s and the C7 forward displacement at 0.35 s after the start of the attack was significantly greater in the elite wrestlers compared to that in the non-elite wrestlers (p < 0.05). This disparity in the C7 forward velocity made a positive contribution in forward displacement by 0.08 m at 0.35 s. Thus, during a double-leg attack, elite wrestlers quickly move their upper body forward while rapidly pushing-off the trailing foot reaching the defender's legs in advance of defensive actions, irrespective of the interpersonal distance. These characteristics may improve the success rate of the double-leg attack.